2018
DOI: 10.4103/jgid.jgid_145_17
|View full text |Cite
|
Sign up to set email alerts
|

Early results of fecal microbial transplantation protocol implementation at a community-based university hospital

Abstract: Introduction:Clostridium difficile (CD) is a serious and increasingly prevalent healthcare-associated infection. The pathogenesis of CD infection (CDI) involves the acquisition of CD with a concurrent disruption of the native gut flora. Antibiotics are a major risk although other contributing factors have also been identified. Clinical management combines discontinuation of the offending antibiotic, initiation of CD-specific antibiotic therapy, probiotic agent use, fecal microbiota transplantation (FMT), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Primary success rate in our institution was 90% (18/20) ( Fig. 1 ) and overall success rate was 100% over a long-term median follow-up period of 25.4 months which is comparable to the rates reported in other studies [ 16 , 18 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 86%
“…Primary success rate in our institution was 90% (18/20) ( Fig. 1 ) and overall success rate was 100% over a long-term median follow-up period of 25.4 months which is comparable to the rates reported in other studies [ 16 , 18 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 86%
“…While most studies reported clinical outcomes according to the CDAD definition and had a similar long-term follow-up, the short-term evaluation of the FMT effect varied. In some studies [45] , the treatment effect was evaluated on day 4 while other [ 44 , 58 ] waited until week 1 after FMT despite ongoing CDAD symptoms. The differences illustrate the difficulties in keeping a balance between overtreatment and preventing disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no one has suggested that the sex of the donor should be considered when screening for suitability as an FMT donor, but the studies in this paper indicate that this could be an important consideration. Indeed, a recent human study found that female sex was associated with failure of FMT to cure C. difficile infection [98]. Advances in methods of cultivation, measurement and preparation of gastrointestinal bacteria are now progressing research from FMT to the development of rationally selected mixtures of bacteria with proven therapeutic efficacy, termed bacteriotherapies.…”
Section: Treatments For Dysbiosis Should Consider the Sex Of The Recimentioning
confidence: 99%